Stohastičko višekriterijsko optimiranje industrijske mikromreže : doktorski rad - Perić, Mario; Tomiša, Tomislav (Zagreb : M. Perić ; Fakultet elektrotehnike i računarstva, 2022)
Doktorski rad pod naslovom Stohastičko višekriterijsko optimiranje industrijske mikromreže rezultat je dugogodišnjeg znanstvenog istraživanja na polju industrijskih kogeneracijskih postrojenja. Znanstveni doprinosi rada su: 1) Definicija funkcije istovremenog trajanja potrošnje električne energije i toplinske energije, 2) Generički model kogeneracijskog postrojenja korištenjem funkcije istovremenog trajanja potrošnje električne energije i toplinske energije i 3) Model za stohastičko višekriterijsko optimiranje industrijske mikromreže korištenjem funkcije istovremenog trajanja potrošnje električne energije i toplinske energije. Rad ima osam poglavlja. Prvo poglavlje daje osvrt na uzroke i ciljeve reforme EES-a te uvodi koncept naprednih mreža kao odgovor na izazove budućeg razvoja EES-a. U drugom poglavlju rada ukratko je opisana problematika planiranja pogona. Treće poglavlje detaljnije obrađuje temu industrijskih mikromreža. U četvrtom poglavlju je predstavljen novi pristup planiranja industrijske mikromreže uvođenjem pojma funkcije istovremenog trajanja potrošnje električne i toplinske energije kao i generičkog model kogeneracijskog postrojenja. Peto poglavlje opisuje kreiranje višekriterijskog modela optimizacije industrijske mikromreže. Zadatak optimizacije je vrednovati moguće opcije sudjelovanja industrijske mikromreže na tržištu električne energije. Predložene su četiri opcije. U šestom poglavlju detaljno je opisan dijagram toka višekriterijskog stohastičkog optimizacijskog postupka. Napravljen je računalni program za demonstraciju, a rezultati su prikazani na kraju poglavlja. U sedmom dodatnim opisom predmeta istraživanja.
The doctoral thesis entitled Stochastic multicriterial optimization of an industrial microgrid is the result of long-term scientific research in the field of industrial cogeneration. The scientific contributions of the thesis are: 1) Definition of the function of the simultaneous duration of electricity and thermal energy consumption, 2) Generic model of a cogeneration plant using the function of the simultaneous duration of electricity and thermal energy consumption and 3) Model for stochastic multicriterial optimization of the industrial microgrid using the function of the simultaneous duration of electricity consumption energy and thermal energy loads. The work has eight chapters. The first chapter overviews the causes and goals of the electric power system (EPS) reform and introduces the concept of advanced networks. In the second chapter the microgrid operation planning issues are briefly described. The third chapter deals with the topic of industrial microgrids in more detail. In the fourth chapter, a new approach to industrial microgrid planning is presented by introducing the concept of the function of the simultaneous duration of electricity and thermal energy loads, as well as a generic model of a cogeneration plant. The fifth chapter describes the creation of a multicriterial industrial microgrid optimization model. The task of optimization is to evaluate options for industrial microgrid participation in the electricity market. Four options are proposed. In the sixth chapter, the flowchart of the optimization procedure is described in detail. A computer program for demonstration was created, the results are presented at the end of the chapter. In the seventh chapter, concluding considerations are presented. The eighth chapter is an appendix where additional description of the research subject is presented.
Bibliografija : str. 205 -219